ChemInform Abstract: Copper‐Mediated Radical Trifluoromethylation of Unsaturated Potassium Organotrifluoroborates. Issue 23 (10th June 2014) - Presset, Marc; Oehlrich, Daniel; Rombouts, Frederik; Molander, Gary A.
Abstract The title reaction allows a simple and mild access to a wide range of unsaturated trifluoromethylated compounds.